Serological Evaluation and Molecular Genotyping of Toxoplasma gondii in Pregnant Women in Meshkin-Shahr District, Northwestern Iran - Shabnam Asfaram; Zabih Zarei; Roghayeh Teimoorpour; Zahra Heidari; Sohrab Iranpour; Payman Azghani; Seyed Eghbal Motavallibashi; Zahra Rakhshidan; Zahra Khademi; Behnam Mohammadi-Ghalehbin; Shahram Habibzadeh; Soheila Molaie (Iranian Journal of Parasitology)
Background: We aimed to investigate the serological and molecular characteristics of Toxoplasma gondii infection among pregnant women and their aborted placentas in Meshkin-Shahr City during 2019-2020. Methods: Blood samples of 210 pregnant women were evaluated for anti-T. gondii antibodies and related risk factors were determined. Also, the sera of aborted women and their buffy coats and aborted placenta tissues were used to detect anti-Toxoplasma antibodies and the parasite’s DNA, respectively. The parasite genotypes were determined by the PCR-RFLP using the SAG3 gene. Results: The overall prevalence of anti-Toxoplasma IgG was 24.3% and only 1% of participants were seropositive for the IgM antibody. There was a significant relationship between raw or unwashed vegetable consumption, contact with soil, vegetable/fruit washing type, and seropositivity (P<0.05). During pregnancy, 4.7% of women encountered an abortion and 30% and 50% of cases were positive for IgG antibodies before and after abortion, respectively. Only two cases were IgM seropositive after abortion. In the avidity IgG test, 20% of cases showed low avidity. BLAST and phylogenetic analysis exhibited that all isolates belonged to the type III T. gondii genotype. Although two women with spontaneous abortions showed seropositivity for IgM T. gondii antibody, parasite DNA was detected in three cases. Conclusion: The seroprevalence of Toxoplasma infection is not high in pregnant women. Seropositive women are not safe from congenital transmission. T. gondii type III is the etiology of fetus infection in mothers with spontaneous abortion. It seems that screening and essential care are still necessary during pregnancy.